多层组合回转筛的动力学仿真分析 Dynamic simulation analysis of multilayer combined rotary screen - 张野，张超，张昊晨，刘海芃，高涛 ZHANG Ye, ZHANG Chao,ZHANG Haochen, LIU Haipeng, GAO Tao (Zhongguo youzhi)
旨在为多层组合回转筛筛体的设计优化及使用调试提供参考，对大产量多层组合回转筛的动力学模型进行了理论分析，推导出了筛体的动力学方程及参数，在此基础上，通过虚拟样机技术进行动力学建模仿真，得到筛体启动运动轨迹及稳定运行轨迹，分析了影响筛体安全(最大振幅)和效率(回转速度、回转半径)关键参数间的关系。结果表明：筛体运动逐渐从椭圆形接近正圆形，正圆的半径即为筛体稳态运行时的回转半径；回转速度与稳定运行过程中的回转半径呈负相关，与启动过程中的最大振幅呈正相关。 To provide a reference for the body design optimization and operational debugging of multilayer combined rotary screen,the dynamic model of large-yield multilayer combined rotary screen was theoretically analyzed, the motion equation and dynamic parameters of the screen body were derived, then the dynamic modeling simulation was carried out through virtual prototyping technology. The transient motion trajectory during the start-up process of the screen body and the motion trajectory during stable operation were obtained, and the relationship between key parameters affecting the safety (maximum amplitude) and efficiency (rotation speed and rotation radius) of the screen body were analyzed.The results indicated that the motion of the screen body gradually transitioned from elliptical to approximately circular. The radius of the perfect circle corresponded to the rotation radius during the steady-state operation of the screen body. The rotation speed was negatively correlated with the rotation radius during stable operation and positively correlated with the maximum amplitude during the start-up process.